Aflatoxins in meals - Pesantes Domínguez, Oswaldo (Revista Universidad de Guayaquil, 2010)
Several grains commonly used in animal and human feeding as corn, rice, wheat, soja and others, could be contaminated by Aspergillis flavus yeast toxic metabolites which usually develop human sicknesses. This contamination is developed during post crop period, carrying and transportation, by unadequated conservation procedures as humidity and high temperature storage. Several reports link direct Aflatoxines relation with hepatic cáncer, however only few meal industries perform quality control techniques to discharge Aflatoxine presence, since there are not legal restrictions or current punish procedures , by this reason, human users follow purchasing and consuming these hazard contaminated grains.